Factorisable Monoid of Generalized Cohypersubstitutions of Type τ=(2): Nagornchat Chansuriya, Sarawut Phuapong - Team, Support (Thai Journal of Mathematics, 2022)
Generalized cohypersubstitutions of type τ = (n_i)_i I are mappings which send n_i-ary cooperation symbols to coterms of type τ. Every generalized cohypersubstitution can be extended to a mapping on the set of all coterms. We define a binary operation on the set of all generalized cohypersubstitutions by using this extension. In this paper, we characterize all unit elements and determine the set of all unit-regular elements of this monoid of type τ = (2). Finally, a submonoid of the monoid of all generalized hypersubstitutions of type τ = (2) which is factorisable is presented.